Young people first! The multiple inscriptions of a generational discourse of Muslimness among Italian-Bangladeshi youths - Priori, Andrea (Migration Letters, 2021)
‘Our parents couldn’t teach us the true meaning of what spirituality and faith can be!’. This assertion, made by a 24-year-old youth, epitomises the critical stance of a group of young Italian-Bangladeshi Muslims towards the religiosity of their former generation. Based on ethnographic research in Rome (Italy), this article illustrates the apparently oxymoronic characteristics of a discourse of Muslimness which, despite stressing the importance of a return to the primary sources of Islam, combines this attitude with a peculiar emphasis on ‘integration’. I will show how this counter-intuitive combination is not only inspired by a scholarly concept of ‘European Islam’, but first and foremost it is grounded in the concrete life conditions of youths who are both well placed within the Italian society and animated by religious zeal. In this way, I seek to shed light on the mutual entanglement of religious stances and life experiences and to point up the limits of ‘exceptionalist’ and ‘literalist’ approaches to the study of Islam.